1964
DOI: 10.1038/bjc.1964.76
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Neoplasia: Sarcomata at the Site of Injection of Cadmium Sulphate in Rats and Mice

Abstract: IN the course of a series of tests of iroii-containing compounds and irolicomplexes for carcinogenicity, it was found that a preparation of rat-ferritin induced not only a high incidence of sarcomata at the site of repeated subcutaneous injection, but also testicular atrophy, Leydig-cell hyperplasia and benign Leydigcell tumours (Haddow, Dukes and Mitchley, 1961 In this paper the induction of sarcomata at the site of subcutaneous injectiol-i of " rat-ferritin " or cadmium sulphate in rats is described and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
34
0
1

Year Published

1965
1965
2009
2009

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 96 publications
(36 citation statements)
references
References 4 publications
1
34
0
1
Order By: Relevance
“…The total dose of cadmium-free ferritin given to the rats in the present investigation (126 mg.) was more than double that of cadmium-precipitated ferritin (56 mg.) used in the previous studies by Haddow and his colleagues (Haddow et al, 1964;Roe et al, 1964). But despite the use of this larger dose, no sarcomas appeared at the site of injection and the testes remained normal.…”
Section: Effects Of Cadmium-freeferritin In Micementioning
confidence: 97%
See 3 more Smart Citations
“…The total dose of cadmium-free ferritin given to the rats in the present investigation (126 mg.) was more than double that of cadmium-precipitated ferritin (56 mg.) used in the previous studies by Haddow and his colleagues (Haddow et al, 1964;Roe et al, 1964). But despite the use of this larger dose, no sarcomas appeared at the site of injection and the testes remained normal.…”
Section: Effects Of Cadmium-freeferritin In Micementioning
confidence: 97%
“…The failure to induce local sarcomas must, however, be interpreted with caution because the survival of many of the rats in the test group was short in relation to the induction-time of sarcomas produced in the earlier experiments with cadmium-precipitated ferritin. Haddow et al (1964), observed the first injection-site sarcoma at 14 months and the average time of appearance of the 7 sarcomas which subsequently developed was over 21 months. On the other hand, the cadmium-free ferritin produced significant fibrosis at the injection-site in only 1 animal; whereas in the earlier experiments, intense proliferation of fibrous tissue was seen in all the test animals, and was palpable in them long before they developed local sarcomas.…”
Section: Effects Of Cadmium-freeferritin In Micementioning
confidence: 99%
See 2 more Smart Citations
“…
THE induction of sarcomas at the site of injection of iron-dextran, of otlher preparations of iron, and of other metal-carbohydrate complexes in rats, mice, hamsters and rabbits is well documented (Richmond, 1957(Richmond, , 1959(Richmond, , 1960Haddow and Horning, 1960; Golberg, Martin and Smith, 1960 ; Lundin, 1961 ;Haddow. Dukes and Mitchley, 1961;Haddow, Roe and Mitchley, 1964;Haddow and Roe, 1964; Roe, Haddow, Dukes and Mitchley, 1964) and has been considered in recent review articles (Roe and Lancaster, 1964;Roe, 1965).

The iron sorbitol-citric acid complex marketed under the name of " Jectofer' has hitherto received less attention from the point of view of carcinogenicitv.

…”
mentioning
confidence: 99%